Докажите,что [latex]ctg ^{2} (2 \pi - \alpha )-sin( \alpha - \frac{ \pi }{2} )* \frac{1}{cos} = \frac{1}{sin ^{2} \alpha } [/latex]
Докажите,что
[latex]ctg ^{2} (2 \pi - \alpha )-sin( \alpha - \frac{ \pi }{2} )* \frac{1}{cos} = \frac{1}{sin ^{2} \alpha } [/latex]
Ответ(ы) на вопрос:
[latex]ctg ^{2} (2 \pi - \alpha )-sin( \alpha - \frac{ \pi }{2} )* \frac{1}{cos\alpha} = \frac{1}{sin ^{2} \alpha } [/latex]
[latex]ctg^{2}\alpha+cos\alpha* \frac{1}{cos \alpha } = \frac{1}{sin ^{2} \alpha } [/latex]
[latex] \frac{cos^{2} \alpha }{sin^{2} \alpha } +1= \frac{1}{sin ^{2} \alpha } [/latex]
[latex] \frac{cos^{2} \alpha +sin^{2} \alpha }{sin^{2} \alpha }= \frac{1}{sin ^{2} \alpha } [/latex]
[latex] \frac{1}{sin^{2} \alpha }= \frac{1}{sin ^{2} \alpha } [/latex] - верно.
Использовались формулы:
1) Основное тригонометрическое тождество: [latex]sin^{2}a+cos^{2}a=1[/latex]
2) Определение котангенса: [latex]ctga= \frac{cosa}{sina} [/latex]
3) Формулы приведения: [latex]ctg(2 \pi -a)=-ctga[/latex]
[latex]ctg^{2}(2 \pi -a)=ctg^{2}a[/latex]
[latex]sin(a- \frac{ \pi }{2})=-cosa[/latex]
Не нашли ответ?
Похожие вопросы